Multi-strategy intervention increases school implementation and maintenance of a mandatory physical activity policy: outcomes of a cluster randomised controlled trial. Issue 7 (26th May 2021) - Nathan, Nicole; Hall, Alix; McCarthy, Nicole; Sutherland, Rachel; Wiggers, John; Bauman, Adrian E; Rissel, Chris; Naylor, Patt-Jean; Cradock, Angie; Lane, Cassandra; Hope, Kirsty; Elton, Benjamin; et al.
Abstract : Objectives: To assess if a multi-strategy intervention effectively increased weekly minutes of structured physical activity (PA) implemented by classroom teachers at 12 months and 18 months. Methods: A cluster randomised controlled trial with 61 primary schools in New South Wales Australia. The 12-month multi-strategy intervention included; centralised technical assistance, ongoing consultation, principal's mandated change, identifying and preparing school champions, development of implementation plans, educational outreach visits and provision of educational materials. Control schools received usual support (guidelines for policy development via education department website and telephone support). Weekly minutes of structured PA implemented by classroom teachers (primary outcome) was measured via teacher completion of a daily log-book at baseline (October–December 2017), 12-month (October–December 2018) and 18-month (April–June 2019). Data were analysed using linear mixed effects regression models. Results: Overall, 400 class teachers at baseline, 403 at 12 months follow-up and 391 at 18 months follow-up provided valid primary outcome data. From baseline to 12-month follow-up, teachers at intervention schools recorded a greater increase in weekly minutes of PA implemented than teachers assigned to the control schools by approximately 44.2 min (95% CI 32.8 to 55.7; p<0.001) which remained at 18 months, however, the effect size was smaller at 27.1 min (95% CI 15.5 to 38.6; p≤0.001). Conclusion: A multi-strategy intervention increased mandatory PA policy implementation. Some, but not all of this improvement was maintained after implementation support concluded. Further research should assess the impact of scale-up strategies on the sustainability of PA policy implementation over longer time periods. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12617001265369).